The Production of Lateness Old Age and Creativity in Contemporary Narrative - Rivera Godoy-Benesch, Rahel (Schweizer Anglistische Arbeiten / Swiss Studies in English, 2020)
This study examines how selected authors of the late 20th and early 21st centuries write about their creative processes in old age and thus purposefully produce a late style of their own. Late-life creativity has not always been viewed favourably. Prevalent "peak-and-decline" models suggest that artists, as they grow old, cease to produce highquality work. Aiming to counter such ageist discourses, the present study proposes a new ethics of reading literary texts by elderly authors. For this purpose, it develops a methodology that consolidates textual analysis with cultural gerontology.